Social-Networks Connect Services. - Ko, Moo Nam; Cheek, Gorrell P.; Shehab, Mohamed; Sandhu, Ravi (Computer (00189162), 2010)
New services such as Facebook Platform, Google Friend Connect, and MySpaceID let third-party sites develop social applications without having to build their own social network. These social-networks connect services increase access to and enrich user data in the Social Web, although they also present several security and privacy challenges.